Individualized positive end-expiratory pressure reduces driving pressure in obese patients during laparoscopic surgery under pneumoperitoneum: a randomized clinical trial - Xavier, Tiago Batista; Coelho, Leonardo Vicente; Ferreira, Daniel Antonio Lopes; Cota y Raposeiras, José Manuel; Duran, Marcelo Sampaio; Silva, Leticia Almeida; Motta-Ribeiro, Gabriel Casulari da; Camilo, Luciana Moisés; Carvalho, Alysson Roncally Silva; Silva, Pedro Leme (Frontiers in Physiology, 2024)
Introduction During pneumoperitoneum (PNP), airway driving pressure (ΔPRS) increases due to the stiffness of the chest wall and cephalic shift of the diaphragm, which favors atelectasis. In addition, depending on the mechanical power (MP) formulas, they may lead to different interpretations. Methods Patients >18 years of age with body mass index >35 kg/m2 were included in a single-center randomized controlled trial during their admission for bariatric surgery by abdominal laparoscopy. Intra-abdominal pressure was set at 15 mmHg at the pneumoperitoneum time point (PNP). After the recruitment maneuver, the lowest respiratory system elastance (ERS) was detected during the positive end-expiratory pressure (PEEP) step-wise decrement. Patients were randomized to the 1) CTRL group: ventilated with PEEP of 5 cmH2O and 2) PEEPIND group: ventilated with PEEP value associated with ERS that is 5% higher than its lowest level. Respiratory system mechanics and mean arterial pressure (MAP) were assessed at the PNP, 5 min after randomization (T1), and at the end of the ventilation protocol (T2); arterial blood gas was assessed at PNP and T2. ΔPRS was the primary outcome. Three MP formulas were used: MPA, which computes static PEEP × volume, elastic, and resistive components; MPB, which computes only the elastic component; and MPC, which computes static PEEP × volume, elastic, and resistive components without inspiratory holds. Results Twenty-eight patients were assessed for eligibility: eight were not included and 20 patients were randomized and allocated to CTRL and PEEPIND groups (n = 10/group). The PEEPIND ventilator strategy reduced ΔPRS when compared with the CTRL group (PEEPIND, 13 ± 2 cmH2O; CTRL, 22 ± 4 cmH2O; p < 0.001). Oxygenation improved in the PEEPIND group when compared with the CTRL group (p = 0.029), whereas MAP was comparable between the PEEPIND and CTRL groups. At the end of surgery, MPA and MPB were correlated in both the CTRL (rho = 0.71, p = 0.019) and PEEPIND (rho = 0.84, p = 0.020) groups but showed different bias (CTRL, −1.9 J/min; PEEPIND, +10.0 J/min). At the end of the surgery, MPA and MPC were correlated in both the CTRL (rho = 0.71, p = 0.019) and PEEPIND (rho = 0.84, p = 0.020) groups but showed different bias (CTRL, −1.9 J/min; PEEPIND, +10.0 J/min). Conclusion Individualized PEEP was associated with a reduction in ΔPRS and an improvement in oxygenation with comparable MAP. The MP, which solely computes the elastic component, better reflected the improvement in ΔPRS observed in the individualized PEEP group. Clinical Trial Registration: The protocol was registered at the Brazilian Registry of Clinical Trials (U1111-1220-7296).